Nucleocytoplasmic Communication in Healthy and Diseased Plant Tissues - Lüdke, Daniel; Rohmann, Philipp F. W.; Wiermer, Marcel (Frontiers in Plant Science, 2021)
The double membrane of the nuclear envelope (NE) constitutes a selective compartment barrier that separates nuclear from cytoplasmic processes. Plant viability and responses to a changing environment depend on the spatial communication between both compartments. This communication is based on the bidirectional exchange of proteins and RNAs and is regulated by a sophisticated transport machinery. Macromolecular traffic across the NE depends on nuclear transport receptors (NTRs) that mediate nuclear import (i.e. importins) or export (i.e. exportins), as well as on nuclear pore complexes (NPCs) that are composed of nucleoporin proteins (NUPs) and span the NE. In this review, we provide an overview of plant NPC- and NTR-directed cargo transport and we consider transport independent functions of NPCs and NE-associated proteins in regulating plant developmental processes and responses to environmental stresses.